2011
DOI: 10.5251/abjna.2011.2.4.720.723
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing rabbits fed graded levels of bovine blood-rumen content mixture

Abstract: A ten-week feeding trial was conducted to assess the growth and economic performance of growing rabbits fed bovine blood-rumen content mixture (BBRCM). The BBRCM which contained 35.4% crude protein and 25.10% crude fibre was included at 0, 10, 20, 30 and 40% levels in diets 1, 2, 3, 4 and 5 respectively to replace groundnut cake in the diets. Forty-five crossbred rabbits (Dutch X New Zealand White) between 5 -7 weeks of age were randomly allocated to the 5 treatments in group of 9 rabbits and allowed unlimited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…Animals have been reported to continue consuming until their energy requirement is met (Südekuma et al, 2004;Esonu et al, 2006). This result agrees with earlier reports from Okpanachi et al (2010) and Mohammed et al (2011) who reported that incorporation of DRD into diets for growing rabbits could increase feed intake at 15.09 to 18.7 g/d when compared to no DRD fed group. Moreover, replacement of SBM with DRD in diets of broilers or Nile Tilapia fish were significantly higher feed intake than those animal fed the control diet (Adeniji and Balogun, 2002;Esonu et al, 2006;Agbabiaka et al, 2011b).…”
Section: Itemsupporting
confidence: 95%
See 1 more Smart Citation
“…Animals have been reported to continue consuming until their energy requirement is met (Südekuma et al, 2004;Esonu et al, 2006). This result agrees with earlier reports from Okpanachi et al (2010) and Mohammed et al (2011) who reported that incorporation of DRD into diets for growing rabbits could increase feed intake at 15.09 to 18.7 g/d when compared to no DRD fed group. Moreover, replacement of SBM with DRD in diets of broilers or Nile Tilapia fish were significantly higher feed intake than those animal fed the control diet (Adeniji and Balogun, 2002;Esonu et al, 2006;Agbabiaka et al, 2011b).…”
Section: Itemsupporting
confidence: 95%
“…Furthermore, it is consisted of the end products of microbes metabolic activities such as microbial protein, amino acids, vitamins, volatile fatty acids (VFA) and contains no anti-physiological factors (Okpanachi et al, 2010), which beneficially affects in the rumen and also enhancing the potential for ruminal microbial activity. Recent studies have shown that replacing SBM by DRD to animal diet improve feed utilization and reducing feed cost in fish (Agbabiaka et al, 2011a(Agbabiaka et al, , 2011b, poultry (Adeniji and Balogun, 2002;Esonu et al, 2006;Esonu et al, 2011), and rabbit (Dairo et al, 2005;Okpanachi et al, 2010;Mohammed et al, 2011Mohammed et al, , 2013. Our previous work has demonstrated that supplementation of DRD at 8 mg in the rations resulted in improved in vitro kinetics gas, rumen fermentation and digestibility in rumen fluid of buffalo (Cherdthong and Wanapat, 2013a).…”
Section: Introductionmentioning
confidence: 95%
“…The feed intakes recorded in all dietary treatments were close to 78.7 g/day [9]; but higher than 53.3–60.4 g/day [10] and lower than 136.3 and 149.9 g/j [11]. The light increase of feed intake of rabbits fed with palm press fibres-based diets (F5, F10 and F15) confirms the statements of [4, 12] according to which, the feed intake is positively correlated with the level of fibre in diet.…”
Section: Discussionmentioning
confidence: 99%
“…Haematological components of the blood are also valuable in monitoring feed toxicity especially with feed constituents that affect the formation of blood (Oyawoye and Ogunkunle, 1998). (Mohammed et al (2010) fed various levels pf bovine blood -rumen content mixture (BBRCM) to growing rabbits and recommended the inclusion of up to 40% BBRCM in their diets without adverse effect on their performance. However, effect of BBRCM on blood parameters is yet to be fully evaluated.…”
Section: Introductionmentioning
confidence: 99%